Annual reporting by social enterprise organizations: "legitimacy surplus" or reporting deficit?. Issue 8 (21st August 2020) - Connolly, Ciaran; Kelly, Martin
Abstract : Purpose: Drawing on an accountability framework developed for social enterprise organizations (SEOs), this paper examines the annual report disclosure practices of SEOs in the United Kingdom in order to investigate the types of accountability disclosed by SEOs. Design/methodology/approach: After developing a SEO database, and utilizing a bespoke document coding checklist, the annual reports of 129 SEOs were examined. Findings: The results indicate that while SEOs would be expected to account in line with normative stakeholder theory, many do not provide constructive and voluntary accountability information to their stakeholders, at least through the annual report, and that their focus is on satisfying legal obligations. Originality/value: In response to calls for research to better understand accountability in new organizational contexts, this paper makes two contributions: firstly, by extending prior accountability research in the NFP sector to consider organizational hybrids, it raises questions about organizational accountability and how it is discharged in situations where an organization operates as a business and yet is accountable for its social mission; secondly, assuming these organizations are driven by their business and social logics, the findings suggest that SEO accountability disclosure practices are inconsistent with the social objectives on which they are based.